Os direitos de liberdade e de igualdade: conquistas, obstáculos e desafios da democracia segundo Norberto Bobbio - Medeiros, Giovanni José de Sousa (2018)
This paper deals with the two fundamental principles of democracy: freedom and equality. It seeks to demonstrate that democratic regimes are characterized by guaranteeing civil and political freedoms and, likewise, they offer themselves as an essential instrument for the promotion of equality and the achievement of social justice. Hence, the various types of freedom expression (autonomy, democratic freedom, positive, negative) reveal, on the same way, the different manners individuals exercise their citizen role in the contemporary corporate context. On equality, it has been shown that only in democracies it is possible to fight for the realization of socio-economic rights. Thus, democracy requires the rule of law tender and the active participation of citizens as a means of enforcing its principles and ensuring the rules of the game. Moreover, the characteristics of representative democracy, the elitism that characterizes it and the fact that it has been the most adequate form of exercising the political power, the struggle for social rights and the guarantees of individual freedoms are highlighted. In spite of the value, importance and civilizational progress represented by democratic regimes, there are still many obstacles, challenges and crossroads that challenge their preservation and advance in the contemporary world.